Pengaruh Implementasi Kurikulum Merdeka Terhadap Kinerja Guru dan Prestasi Belajar Pendidikan Agama Islam dan Budi Pekerti Siswa SMAN 2 Kaur - Neca Gemelia (Al-Bahtsu: Jurnal Penelitian Pendidikan Islam, 2024)
The research objectives are 1) to determine the influence of the implementation of the independent curriculum on the performance of Islamic Religious Education and Character Education teachers at SMA Negeri 2 Kaur. 2) to determine the effect of the implementation of the independent curriculum on the learning achievement of Islamic Religious Education and Character of SMA Negeri 2 Kaur students. This type of research is quantitative with an associative approach. Data collection techniques are observation, questionnaires and documentation. The research sample used Probality Sampling with the Stratified Random Sampling technique. The research results show that 1) There is a significant influence between the implementation of the independent curriculum on teacher performance in learning Islamic Religious Education and Character at SMA Negeri 2 Kaur. This is proven from the t-count > t-table (5.262 > 1.645). 2) There is a significant influence between the implementation of the independent curriculum and student learning achievement in learning Islamic Religious Education and Character. This is proven from t-count > t-table (5.583 > 1.645).